"Plange, Castella misera": meaning and mourning at the royal abbey of Las Huelgas de Burgos in the late twelfth and early thirteenth centuries. Issue 1 (2nd January 2020) - Henry, Emily
ABSTRACT: Royal burial sites, besides functioning as resting places for rulers, offer repositories of emotions associated with royal death. One such site was the abbey of Las Huelgas de Burgos, founded in 1187 by Alfonso VIII of Castile and Leonor of England, which served as their and their children's burial site. Just as it housed their bones, Las Huelgas also housed the record of royal grief, displayed in laments and tombs within the abbey. These sources, alongside contemporary chronicles, describe acts of mourning performed at the abbey during the early decades of Las Huelgas' existence (1187–1214). They reveal public displays of grief by the royal family and on their behalf. This royal grief functioned on an individual and corporate scale, the collective mourning of the kingdom intersecting with the emotional reactions of the Castilian rulers. This article, adopting the perspective of the history of emotions, demonstrates that the expressions of royal grief at Las Huelgas were not only imbued with dynastic and religious significance but revealed the complex interactions between individual grief and collective rituals of mourning. These demonstrations of emotion displayed the collaboration between rulers and their subjects in constructing and memorializing royal grief in twelfth and thirteenth-century Castile.